2013
DOI: 10.1159/000355169
|View full text |Cite
|
Sign up to set email alerts
|

Ivabradine Improves Quality of Life in Subjects with Chronic Heart Failure Compared to Treatment with β-Blockers: Results of a Multicentric Observational APULIA Study

Abstract: Objectives: Ivabradine (IVA), a selective If current inhibitor decreasing the heart rate (HR) in patients with sinus rhythm, has been added to the most recent European Guidelines on heart failure. This selective treatment reduces HR exclusively while fully preserving myocardial contractility and relaxation, atrioventricular conduction, and ventricular repolarization, as well as blood pressure. The aim of this study was to evaluate the improvement of quality of life (QOL) in patients with chronic hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 19 publications
1
13
0
1
Order By: Relevance
“…These results are supported by a study by Riccioni et al [25] and also a head-to-head comparison trial of ivabradine, carvedilol, or combination treatment [15], demonstrating greater improvement in QOL with ivabradine alone or with combination therapy with carvedilol compared with carvedilol alone. In this head-to-head study, Volterrani et al [15] found no significant effect of carvedilol monotherapy on QOL after 3 months of treatment versus baseline.…”
Section: Discussionsupporting
confidence: 69%
“…These results are supported by a study by Riccioni et al [25] and also a head-to-head comparison trial of ivabradine, carvedilol, or combination treatment [15], demonstrating greater improvement in QOL with ivabradine alone or with combination therapy with carvedilol compared with carvedilol alone. In this head-to-head study, Volterrani et al [15] found no significant effect of carvedilol monotherapy on QOL after 3 months of treatment versus baseline.…”
Section: Discussionsupporting
confidence: 69%
“…Guideline-recommended HF medication is clearly focused on prolongation of life, but much less on improving QoL:119,120 ACE inhibitors and ARBs,120 beta-blockers114,119121 and also the aldosterone antagonist eplerenone122 are neutral, or only modestly improve or at best delay the progressive worsening of QoL.…”
Section: Patient Focus Perspectives: Quality Of Life (Qol)mentioning
confidence: 99%
“…in ivabradine group and 72 ± 4 b.p.m. in beta-blocker group) 119. According to the new HF classification of the ESC,3 these patients would now be classified as patients with HFmrEF.…”
Section: Patient Focus Perspectives: Quality Of Life (Qol)mentioning
confidence: 99%
“…There is now much evidence for the use of ivabradine to improve quality of life in symptomatic HF patients, who may have dyspnea at rest or on effort, altered exercise capacity, and fatigue [ 21 , 23 , 26 , 27 ], all of which may improve in the first weeks of therapy. In a sub-analysis of SHIFT (Systolic Heart failure treatment with the I f inhibitor ivabradine Trial) [ 28 ] in 1944 patients, health-related quality of life, as recorded by the disease-specific Kansas City Cardiomyopathy Questionnaire, was found to be inversely associated with clinical events [ 26 ].…”
Section: Effect Of Ivabradine On Quality Of Lifementioning
confidence: 99%